Al-'Arabiyyah Baina Yadaik Book Speaking Skill Material Based On Common European Framework of Reference (CEFR) - Muhammad Zahid 'Afifarrasyihab Rahimadinullah Samsudin; Imam Asrori; Hanik Mahliatussikah; Alaualdeen Ahmad Muhammad Algharibeh (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2023)
This research was conducted with the purpose of describing scope of speaking skill material including theme, functional competency, and types of text exercises and describing level of speaking skill material in Al-‘Arabiyyah Baina Yadaik (ABY) book volume 1 based on the Common European Framework of Reference (CEFR). Approach used in this research is descriptive qualitative approach with the type of library research. The data collection technique used is documentation technique. The analysis technique used is content analysis technique. The result of this research showed that: (a) speaking skill material about theme includes 7 major themes, functional competence includes 5 main functions, and there are 5 types of text exercises in general, (b) ABY 1 book speaking skill materials are at level A1-B1 based on the CEFR.